A COMPARATIVE LINGUISTIC ANALYSIS OF CROSS-CULTURAL MEANINGS IN PROVERBS - Khasanova Dilnoza (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
This paper explores the linguistic and cultural layers embedded in proverbs across different societies, focusing on their comparative semantic structures, pragmatic functions, and symbolic meanings. Drawing on examples from English, Uzbek, Chinese, and Arabic proverbial systems, the article examines how language reflects cultural cognition, value systems, and worldview. The analysis emphasizes both universal themes and culturally specific nuances, highlighting the role of proverbs as repositories of collective wisdom and identity. The paper also addresses challenges in translation and interpretation of proverbs in intercultural communication and language teaching.